4GR joining hands (hunger's heroes machine) / Nurul Nadhirah Mohd Rosli...[et al.] - Mohd Rosli, Nurul Nadhirah; Zaini, Nur Ain Syuhada; Kamarul Zaman, Nur Fatiehah; Mat Rosly, Nur Aliyah (2019)
The product to be developed is a Hunger's Heroes Machine. It is common knowledge that Malaysia is one of the countries that have a high rate of poverty, especially in rural areas. Based on the article 'Poverty rate of rural and urban areas in Malaysia from 2007 to 2016', the statistics had shown that most of the poverty rate was in rural areas and the maximum rate at 8.4% in 2009, (Hirschmann, 2019). According to the info from the Department of Statistics Malaysia, Sabah recorded as the maximum of the incidence of poverty in 2009 and 2012. The poverty is living in an extreme condition where they had ever cut the size of meals or skip because there is no money to buy the food. To reduce the burden of poverty, the team is developing Hunger's Heroes Machine which comes from the vending machine as a first idea before developing it with new features. The vending machine has been remodelled to staple food such as rice, flour and cooking oil to those in need. This may reduce their difficulties to get enough food daily and able to stay alive with good health.